2014
DOI: 10.1016/j.bbadis.2013.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Stressing on the nucleolus in cardiovascular disease

Abstract: The nucleolus is a multifunctional organelle with multiple roles involving cell proliferation, growth, survival ribosome biogenesis and stress response signaling. Alteration of nucleolar morphology and architecture signifies an early response to increased cellular stress. This review briefly summarizes nucleolar response to cardiac stress signals and details the role played by nucleolar proteins in cardiovascular pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 64 publications
0
30
0
1
Order By: Relevance
“…It is an organization of multiple-component complexes of nucleic acid and proteins, including tandemly repeated copies of rDNA for rRNA genes, RNA polymerase I (Pol I, one of the three RNA polymerases) that exclusively transcribes rDNA (Goodfellow and Zomerdijk, 2013) and factors involved in ribosome biogenesis, which is coupled to the transcription of rRNA genes. Malfunction in Pol I transcription of rRNA genes and abnormality in rDNA clusters are common features in cancer cells and human diseases (Hariharan and Sussman, 2014; Peltonen et al, 2014; Quin et al, 2014; van Sluis and McStay, 2014). …”
Section: Differences In Genome Organization Transcription Machinery mentioning
confidence: 99%
“…It is an organization of multiple-component complexes of nucleic acid and proteins, including tandemly repeated copies of rDNA for rRNA genes, RNA polymerase I (Pol I, one of the three RNA polymerases) that exclusively transcribes rDNA (Goodfellow and Zomerdijk, 2013) and factors involved in ribosome biogenesis, which is coupled to the transcription of rRNA genes. Malfunction in Pol I transcription of rRNA genes and abnormality in rDNA clusters are common features in cancer cells and human diseases (Hariharan and Sussman, 2014; Peltonen et al, 2014; Quin et al, 2014; van Sluis and McStay, 2014). …”
Section: Differences In Genome Organization Transcription Machinery mentioning
confidence: 99%
“…Na slici 1 apeks krivulje učestalosti AgNOR publikacija, u kojima se prvenstveno radi o tumorskoj patologiji, ukazuje na nagli porast interesa za funkciju ribosomalnih gena u onkogenezi i uvod je u istraživanje jezgrice dinamičkim molekularnim metodama na ulazu u 21. stoljeće kada dolazi do promjene definicije jezgrice. Povezivanjem oblika, strukture i funkcije AgNOR metoda ukazuje na razvoj znanstvene misli, te daje uvid u povezanost jezgrice s patološkim stanjima koja su danas opisana molekularnim metodama [76][77][78][79][80]111,[122][123][124][125][126][127][128][129][130][131][132] . Time patologija, molekularna biologija i biotehnologija dobivaju zajednički cilj istraživanja: jezgricu u bolesti, što je vidljivo i ovdje u slici 1 i 2, a u čemu među prvima sudjeluju znanstvenici Medicinskog fakulteta u Rijeci 132 .…”
Section: Grupa Za Agnor I Rezultati S Apeksomunclassified
“…[20] demonstrated that overexpression of nucleostemin in human adult CPCs antagonizes their senescence by decreasing the number of senescent and multinucleated cells, and by restoring a youthful cell morphology. Nucleostemin is a nucleolar protein activated downstream of Pim-1 and is known to regulate ribosomal biogenesis, proliferation and growth of stem cells [21]. Given their efficacy in antagonizing hCPC senescence, Pim-1 and nucleostemin constitute promising candidates for future interventional approaches to restore reparative potential in the aged failing heart.…”
Section: Strategies To Rejuvenate the Senescent Heartmentioning
confidence: 99%